Radiographic Assessment of Bone Width Improvement in Narrow Ridge Patients Managed with Ridge Split Technique: A Prospective Study - Bhavya Sharma; Vilas P. Newaskar; Deepak Agrawal; Ayushi Patidar; Deepak K. Khareliya; Harshita Sachdev; Ranjana Sharma (Journal of Pharmacy and Bioallied Sciences)
Background: Endosseous implant insertion is often hindered by narrow dentoalveolar ridges, necessitating various techniques like guided bone regeneration, bone block grafting, and ridge splitting for bone expansion. Ridge splitting offers a less invasive method, allowing predictable expansion and grafting using bone allografts. Piezosurgery, uses ultrasonic vibrations, enables precise and clean bone incisions during this procedure. Aims: To evaluate the improvement in bone width using the ridge split technique in the narrow mandibular posterior region. Material and Method: A prospective study was conducted after valid approval of ethics committee of the institution. The study included 34 sites among 28 patients aged 16–50 years. The sample size was calculated using G Power software, and all participants provided informed consent. Preoperative ridge width measured using CBCT, ridge split done, and expansion achieved. Created space filled with sticky bone graft. Gain in width measured with CBCT after 3 months. Data were analyzed using SPSS 21.0. The Kolmogorov–Smirnov test assessed probability distribution. Intergroup comparisons were made using the independent “t” test or Mann–Whitney U test, while intragroup comparisons used the paired “t” test or Wilcoxon signed rank test. The Chi-square test was used for categorical variables, with a P value <0.05 considered statistically significant. Results: A statistically significant increase in bone width was observed at the alveolar crest and 3 mm and 6 mm below the crest at three months postoperatively, i.e., from 3.623 + 0.578 to 4.235 + 0.596, from 6.284 + 0.959 and 7.145 + 1.194, and from 8.412 + 1.167 to 9.165 + 1.198, respectively. Conclusions: The ridge split technique is effective in increasing bone width in the narrow mandibular alveolar ridge. It presents a less invasive and cost-effective alternative to traditional ridge augmentation methods. However, the study’s limitations include a small sample size and a shorter monitoring period. Further studies with larger samples and longer follow-up are recommended to confirm these findings.